E-GOVERNMENT MATURITY LEVEL ANALYSIS (STUDY ON 35 GOVERNMENT WEBSITES IN CENTRAL JAVA) - Surya, Hendrawan Bintang; Nugroho, Rino Ardhian (Natapraja, 2022)
This study examines maturity level of E-Government in 35 websites government in Province Central Java. The reason for choosing the location of Central Java Province is the province has a high ICT Development Index (IP-TIK) but not in line with the high Indonesian e-government rating either. So that measuring the maturity of websites in all 35 cities in Central Java Province is important so that these regions make improvements This study uses a government maturity model, there are 5 variabels: Simple Information, Two-way Communication, Service and Financial Transaction, Integration and Political Participation. This study method uses a quantitative approach. Then, This study uses descriptive statistical analysis techniques. The result of this study is 35 websites government in Province Central Java has a level of immature maturity model. With details that of the five variables, 2 of them have a very low level of maturity and 1 of them has a medium maturity level.